Effects of Instant Messaging on School Performance in Adolescents. (June 2016) - Grover, Karan; Pecor, Keith; Malkowski, Michael; Kang, Lilia; Machado, Sasha; Lulla, Roshni; Heisey, David; Ming, Xue
Instant messaging may compromise sleep quality and school performance in adolescents. We aimed to determine associations between nighttime messaging and daytime sleepiness, self-reported sleep parameters, and/or school performance. Students from 3 high schools in New Jersey completed anonymous questionnaires assessing sleep duration, daytime sleepiness, messaging habits, and academic performance. Of the 2, 352 students sampled, 1, 537 responses were contrasted among grades, sexes, and messaging duration, both before and after lights out. Students who reported longer duration of messaging after lights out were more likely to report a shorter sleep duration, higher rate of daytime sleepiness, and poorer academic performance. Messaging before lights out was not associated with higher rates of daytime sleepiness or poorer academic performance. Females reported more messaging, more daytime sleepiness, and better academic performance than males. There may be an association between text messaging and school performance in this cohort of students.